Bio-Mimicking, Electrical Excitability Phenomena Associated With Synthetic Macromolecular Systems: A Brief Review With Connections to the Cytoskeleton and Membraneless Organelles - Wnek, Gary E.; Costa, Alberto C. S.; Kozawa, Susan K. (Frontiers in Molecular Neuroscience, 2022)
Electrical excitability of cells, tissues and organs is a fundamental phenomenon in biology and physiology. Signatures of excitability include transient currents resulting from a constant or varying voltage gradient across compartments. Interestingly, such signatures can be observed with non-biologically-derived, macromolecular systems. Initial key literature, dating to roughly the late 1960’s into the early 1990’s, is reviewed here. We suggest that excitability in response to electrical stimulation is a material phenomenon that is exploited by living organisms, but that is not exclusive to living systems. Furthermore, given the ubiquity of biological hydrogels, we also speculate that excitability in protocells of primordial organisms might have shared some of the same molecular mechanisms seen in non-biological macromolecular systems, and that vestigial traces of such mechanisms may still play important roles in modern organisms’ biological hydrogels. Finally, we also speculate that bio-mimicking excitability of synthetic macromolecular systems might have practical biomedical applications.